The 'Finding Kite' teacher guide - Holmes, Rachel (Special educational needs coordinator) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This teacher resource is filled with worksheets, tasks and activities focused on developing the social skills of autistic children aged 8-12. It has been created to be used alongside the story Finding Kite: An Interactive Tudor Mystery, although activities can stand alone as a programme of intervention. Each task encourages young people to think about their own experiences, challenges and goals, building self-esteem and confidence along the way. Suitable for use in small groups or 1:1, the worksheets are flexible in design, allowing the facilitator to respond to the needs of each child. Key features of this resource include: Engaging activities divided into sections focused on 'Making Sense of my World' and 'Connecting with Others'; Photocopiable and downloadable worksheets, filled with opportunities for reflection and discussion; The option to use it alongside the engaging, choose your own adventure story, Finding Kite, which immerses the reader in a sensory adventure. Designed for students aged 8-12, this resource provides an invaluable opportunity to build an understanding of the complexities of social dynamics. Although created with autistic girls in mind, it can be used with students of different genders and adapted for their needs"--
Making sense of my feelings (anger, anxiety, worry, fear) -- Making sense of my environment (stressful/relaxing places, sensory information) -- Making sense of what I hear (verbal processing, communication skills, idioms) -- Making sense of what I see (facial expressions, body language) -- Me (promoting positive sense of self) -- Making connections (interactions with others, friendship) -- Managing difference and disagreement.
OCLC-licensed vendor bibliographic record.
Keywords: Social skills -- Study and teaching (Elementary); Social skills in children; Decision making -- Study and teaching (Elementary); Decision making in children; EDUCATION / General; EDUCATION / Elementary; EDUCATION / Special Education / General